Designing gamified systems meaningful play in interactive entertainment, marketing and education - Gilbert, Sari (Focal Press, 2016)
Designing Gamified Systems is a fundamental guide for building essential skills in game and interaction design to revitalize and reimagine real world systems - from cities and corporations to schools and the military. Author Sari Gilbert develops a set of core principles and tools for using game thinking and interactive design to build motivation, explain hard concepts, broaden audiences, deepen commitments and enhance human relationships